(untitled) (Al-Mansour Journal, 2022)
There are many methods for solving linear programming problems with unrestricted variables that gets the optimal solution of the problem where the values of variables are fractional numbers not integer numbers, But when there are conditions in the problem that requires the result is optimal integer solution, that is the resulted variables values was numerical integer, At that time we must turn to a method that we get from it the integer solution of the problem. That is the subject of the research where we will employ an algorithm of the method (Modify Surrogate Cutting Plane algorithm) to solve linear integer programming problems that to find integer solution of linear programming problems with unrestricted variables that after getting a view at linear Programming with unrestricted variables and Integer Programming.